2016
DOI: 10.1016/j.bbabio.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-bound electron transport systems of an anammox bacterium: A complexome analysis

Abstract: Electron transport, or oxidative phosphorylation, is one of the hallmarks of life. To this end, prokaryotes evolved a vast variety of protein complexes, only a small part of which have been discovered and studied. These protein complexes allow them to occupy virtually every ecological niche on Earth. Here, we applied the method of proteomics-based complexome profiling to get a better understanding of the electron transport systems of the anaerobic ammonium-oxidizing (anammox) bacteria, the N2-producing key pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 83 publications
3
79
0
Order By: Relevance
“…In some planctomycetes, the genes encoding proteins of this family are found within the operons of cyt bc complexes (Kartal et al 2011, Dibrova et al 2013. De Almeida et al (2016) have recently shown that in Ca. K. stuttgartiensis such protein complexes, which contain both the cyts b and large oxidoreductase subunits, are expressed at high levels.…”
Section: Modular Assembly Of Ancestral Cyt Bc Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…In some planctomycetes, the genes encoding proteins of this family are found within the operons of cyt bc complexes (Kartal et al 2011, Dibrova et al 2013. De Almeida et al (2016) have recently shown that in Ca. K. stuttgartiensis such protein complexes, which contain both the cyts b and large oxidoreductase subunits, are expressed at high levels.…”
Section: Modular Assembly Of Ancestral Cyt Bc Complexesmentioning
confidence: 99%
“…This evolutionary scenario has been recently challenged (Kao and Hunte , Ducluzeau and Nitschke ). In the view of new important data (Bergdoll et al , de Almeida et al ) and a dramatic increase in the number of sequenced genomes, we revisit here the evolutionary history of the cyt bc complexes and present an updated phylogenomic analysis of the cyt b subunits. We show that new genomic data provide further support to our earlier suggestion on the evolutionary primacy of cyt bc complexes with small cyts b .…”
Section: Introductionmentioning
confidence: 99%
“…The resulting heat maps allow the identification of proteins forming part of protein complexes. Although introduced only relatively recently, this strategy has already added an additional degree of depth to the systematic identification of protein complexes in cells or subcellular fractions, albeit so far mainly in mammals (Heide et al ., ; Takabayashi et al ., ; Wessels et al ., ; De Almeida et al ., ; Huynen et al ., ; Müller et al ., ; Prior et al ., ; Wöhlbrand et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Recently, mass spectrometry based metaproteomic approaches are attracting particular attention for discovering microbial functions in mixed culture systems (Barr et al, 2015;Mosier et al, 2015;de Almeida et al, 2016;Salerno et al, 2016). mRNA levels can respond rapidly and sensitively to environmental conditions changes, while changes in protein abundances can be comparatively much slower (Zhu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%